Assessment of the conservation status of the mat-forming lichens Cladonia subgenus Cladina in Italy. (2nd September 2016) - Ravera, S.; Isocrono, D.; Nascimbene, J.; Giordani, P.; Benesperi, R.; Tretiach, M.; Montagnani, C.
Abstract : Cladina species are likely to suffer the impact of human pressure, resulting in a potential, as well as currently unknown, extinction risk for some of them. In this study, we used herbarium specimen data and literature data combined with geographic information system (GIS)-based analyses to assess the threatened status of Italian Cladina species according to IUCN criteria. A total of 485 records, reported during the period 1833–2013, were evaluated. Biological traits, habitat requirements and distribution patterns were used to infer species extinction risk. Extent of occurrence and area of occupancy have been calculated at the national scale, based on a 2 km × 2 km cell grid. The potential threats for the taxa were assessed using a decision-support protocol in order to set conservation targets for taxa lacking population viability analyses and habitat modelling data. The species were assigned to the IUCN categories mainly using the geographical criterion B, related to species with restricted and fragmented distribution and continuous declining trend, but the species have been tested against the maximum number of criteria for which data were available and/or appropriate. This has provided an opportunity to discuss some basic aspects of the process of lichen red-listing, suggesting some methodological improvements for the mat-forming ones.